The Effectiveness of Online Learning on Students’ TPACK based Teaching Instrument - Yanti Suryanti; Teti Rostikawati; Sandi Budiana (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The aim of the study is to depict the effectiveness of online learning on the students’ ability to write TPACK based teaching instruments during the pandemic. The subjects of the research were 15 students of pre-service student-teacher candidates of the Faculty of Teacher Training and Educational Science, Pakuan University, the academic year 2020-2021. The approach of the study is quantitative with questionnaires, and documents as the instruments. The result of the study shows that online learning has not reached the maximum effect on the students’ ability to write TPACK-based teaching instruments, although the result is considered fair. Meanwhile, the teachers still need to get the knowledge on how to integrate materials using digital applications and mix them into interesting teaching materials and media.